Pengaruh Working Capital to Total Asset dan Total Asset Turnover terhadap Laba Bersih Pada PT. Akasha Wira Internasional Tbk. - Alfisahr, Siti Nur; Muniarty, Puji (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This research was conducted at PT. Akasha Wira Internasional Tbk. With the aim to find the effect of working capital to total assets and total asset turnover on profits at pt. akasha wira international. The type of research used in this research is associative. The research instruments used in this study are financial reports including cash flow statements, income statements and balance sheets. The sample used in this study is the financial statements of PT. Akasha Wira International for 10 years from 2012-2021. The analytical techniques used in this study are financial analysis including WCTA analysis, TATO analysis, classical assumption analysis: normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, multiple linear regression analysis, multiple correlation analysis, multiple determination, t test and test f. The results of this study are that both working capital to total assets and total asset turnover have no partial effect on profits, and working capital to total assets and total asset turnover together have no simultaneous effect on profits at Pt. Akasha Wira International.